Au Nanoclusters Ameliorate Shigella Infectious Colitis by Inducing Oxidative Stress - Wu X (Dove Medical Press, 2021)
Xiaoxiao Wu,1,* Yongyan Chen,1,* Yangheng Zhang,2,* Yunjie Shan,1 Zhiyue Peng,1 Bing Gu,1,3 Huan Yang1 1Xuzhou Key Laboratory of Laboratory Diagnostics, School of Medical Technology, Xuzhou Medical University, Xuzhou, 221004, People’s Republic of China; 2Department of Periodontology, Nanjing Stomatological Hospital of Nanjing University School of Medicine, Nanjing, 210008, People’s Republic of China; 3Laboratory Medicine, Guangdong Provincial People’s Hospital, Guangdong Academy of Medical Sciences, Guangzhou, Guangdong, 510000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huan Yang; Bing Gu Email yanghuan2015@tmu.edu.cn; gb20031129@163.comBackground: Shigella infection has always been a global burden, and it particularly threatens children between the ages of 1 and 5 years. Economically underdeveloped countries are dominated by Shigella flexneri infection. The most effective method to treat Shigella is antibiotics, but with the abuse of antibiotics and the prevalence of multidrug resistance, we urgently need a relatively safe non-antibiotic treatment to replace it. Ultrasmall Au nanoclusters (NCs) have special physical and chemical properties and can better interact with and be internalized by bacteria to disrupt the metabolic balance. The purpose of this study was to explore whether Au NCs may be a substitute for antibiotics to treat Shigella infections.Methods: Au NCs and Shigella Sf301, R2448, and RII-1 were cocultured in vitro to evaluate the bactericidal ability of Au NCs. The degree of damage and mode of action of Au NCs in Shigella were clearly observed in images of scanning electron microscopy (SEM). In vivo experiments were conducted to observe the changes in body weight, clinical disease activity index (DAI) and colon (including length and histopathological sections) of mice treated with Au NCs. The effect of Au NCs was analysed by measuring the content of lipocalin-2 (LCN2) and Shigella in faeces. Next, the changes in Shigella biofilm activity, the release of reactive oxygen species (ROS), the changes in metabolism-related and membrane-related genes, and the effect of Au NCs on the body weight of mice were determined to further analyse the mechanism of action and effect.Results: Au NCs (100 μM) interfered with oxidative metabolism genes, induced a substantial increase in ROS levels, interacted with the cell membrane to destroy it, significantly killed Shigella, and effectively alleviated the intestinal damage caused by Shigella in mice. The activity of the biofilm formed by Shigella was reduced.Conclusion: The effective antibacterial effect and good safety suggest that Au NCs represent a good potential alternative to antibiotics to treat Shigella infections.Keywords: Shigella, Au nanoclusters, antibacterial effect, reactive oxygen species, oxidative stress